Obesity and clotting. Issue 1 (January 2015) - Kornblith, Lucy Z.; Howard, Benjamin; Kunitake, Ryan; Redick, Brittney; Nelson, Mary; Cohen, Mitchell Jay; Callcut, Rachael
<x xml:space="preserve">Abstract</x> BACKGROUND Although obese patients have high thrombosis rates following injury, the role of obesity in coagulation after trauma remains unknown. We hypothesized that body mass index (BMI) is independently associated with increased measures of hypercoagulability longitudinally after injury. METHODS Data were prospectively collected for 377 consecutive highest-level trauma activation patients with a BMI of 18.5 kg/m2 or greater. Standard coagulation measures, citrated kaolin and functional fibrinogen thromboelastography, as well as clotting factors were measured at 0 hour to 120 hours. BMI categories were defined as normal weight (18.5–24.99 kg/m2), overweight (25–29.99 kg/m2), and obese (≥30 kg/m2). RESULTS The 377 patients were mostly male (81%) and had blunt injury (61%), with a median BMI of 25.8 kg/m2. Of the patients, 42% were normal weight (median BMI, 22.5 kg/m2). There were no differences in age, sex, Injury Severity Score (ISS), or base deficit between groups. There were no differences in admission international normalized ratio/partial thromboplastin time or factors II, V, VII, VIII, and X; antithrombin III; or protein C. However, obese patients had higher admission platelet counts (303 × 109/L vs. 269 × 109/L, p = 0.004), lower D-dimer (1.88 μg/mL vs. 4.00 μg/mL, p = 0.004), and a trend toward higher factor IX (134% vs. 119% activity, p = 0.042) compared with normal weight patients. Measured by thromboelastography, clot strength (maximum amplitude) and functional fibrinogen level (FLEV) were also higher on admission for obese patients (maximum amplitude, 65.7 mm vs. 63.4 mm, p = 0.016; FLEV, 407 mg/dL vs. 351 mg/dL, p = 0.008). In multiple linear regression, the relationship of BMI to clot strength, FLEV, and factor IX persisted through 24 hours. Similarly, the relationship of BMI and platelet count persisted through 120 hours (all p < 0.05). In multiple logistic regression, for every 5-kg/m2 increase in BMI, there was an 85% increase in odds of thromboembolic complication (odds ratio, 1.85; 95% confidence interval, 1.13–3.08; p = 0.017). CONCLUSION Obese trauma patients are hypercoagulable compared with their similarly injured normal-weight counterparts, which persists longitudinally after injury. The significance of this hypercoagulability requires elucidation for guidance of anticoagulation in this at-risk group. LEVEL OF EVIDENCE Prognostic study, level III.